Assesseing the Effect of Polypropylene Plastic on the Durability of Asphalt Pavements - Noble Ruhinda Ankunda (Uganda Christian University, 2025)
Flexible pavements are roads comprising of a surfacing layer comprising of bitumen aggregate and filler. The purpose of this report is to present a study conducted to create a resilient asphalt mixture for the durability of asphalt pavements. The significant existence of early pavement failures in the form of cracking and rutting was the major drive for this study. A modified asphalt mixture made using polypropylene plastic was proposed and tested in evaluation against the conventional asphalt mixture. This goal was achieved by conducting mechanical tests on materials that were used that is the aggregates and bitumen and characterisation of the polypropylene plastic. Other tests included the marshal tests and indirect tensile stress tests on both the modified asphalt and conventional asphalt samples to show the improvement caused by incorporating polypropylene plastic. Coating aggregates with polypropylene plastic led to a reduction in the Average Crushing Value from 15.8% to 13.6%. This signified an improvement in mechanical properties of coated aggregates. Marshall Quotient increased by 0.3, Air voids reduced by 0.5% and Indirect Tensile Strength (ITS) ratio increased to 96% from 87%. These tests also identified that 3% polypropylene plastic modification improved the general properties of asphalt especially making the asphalt mixture more resistant to moisture damage, heat and cracking. However, there is need for more research in the use of other types of plastic in asphalt mixture in order to ascertain the full potential of polymer modified asphalt.